Study Of the compression behaviours of 3D-printed PEEK/CFR-PEEK sandwich composite structures - Houfeng Jiang; Patiguli Aihemaiti; Wurikaixi Aiyiti; Ayiguli Kasimu (Virtual and Physical Prototyping, 2022)
Single-component materials and homogeneous structures cannot adequately meet the various demands of ideal bone implants. Therefore, the use of three dimensional (3D) printing to form multi-materials and composites has received considerable attention owing to its potential to achieve multiple functions and properties in different areas. In this study, composite structures of polyetheretherketone (PEEK) and carbon-fibre-reinforced polyetheretherketone (CFR-PEEK) materials were designed and printed. Compression experiments were conducted to investigate the effects of the building orientation on the compression strength and failure mode. Micro-X-ray detection was conducted to observe the specimen's internal microstructures. Full-field strain monitoring was performed to measure the strain fields of the specimens. The results showed that the building orientation had a significant influence on the interface bonding quality and failure modes of the specimens. The Flat specimen exhibited the lowest compressive strength of 69.1 MPa because of the poor fusion of the bottom interface. The On-edge specimen showed a higher strength of 71.5 MPa, and interlayer tearing was the main failure mode. The Up-right specimen exhibited the largest compressive strength of 80.4 MPa. After applying the interlayer inset and in-layer inset methods, the compressive strengths of the Up-right specimen improved by 16.4% and 37.4% respectively.